Inflation targeting : design, performance, challenges - Loayza, Norman; Soto, Raimundo; Banco Central de Chile; Banco Central de Chile (Santiago : Central Bank of Chile, 2002)
The book demonstrates that inflation targeting can be implemented in the real world of flexible exchange rates and open capital markets b small and large open economies. It is a collection of empirical and theoretical studies of ten years of inflation targeting, covering design, performance and challenges.
"Most studies included here are substantially revised versions of papers presented at the Fourth Annual Conference of the Central Bank of Chile, on "10 Years of Inflation Targeting: Design, Performance, Challenges," held in Santiago in November 2000."--P. 2.
Includes bibliographical references.
oif 17/09/2019
Loans
Keywords: Inflation targeting; Inflation (Finance)